Exploring the Tripartite Performance in the Musical Enculturation: An Ethnographic Study of Banyumasan Sinden - Suharto, Suharto; Sugiyanto, Sugiyanto; Chan, Clare Suet Ching (Institut Seni Indonesia Yogyakarta, 2025)
This study examines the musical enculturation of Banyumasan sinden across three performance genres: wayang kulit, lengger calung, and ebeg. Using Merriam’s tripartite model – musical concept, behavior, and sound – as the analytical framework, this research explores how different learning trajectories and social contexts shape the formation of musical identity. Employing an ethnographic approach, this study analyzes field data gathered through interviews, observations, and documentation of sinden practices in rural and semi-urban area of Banyumas. Findings reveal that wayang sindens develop their skills through vertical cultural transmission within artist families, reinforcing ethical and aesthetic ideals. In contrast, lengger sindens engage in horizontal, community-based learning characterized by participatory interaction and vocal expressiveness. Meanwhile, ebeg sindens follow a situational, adaptive learning model shaped by informal performance settings and pragmatic vocal function. The study concludes that each sinden tradition reflects a distinct pattern of enculturation rooted in its socio-performative context, and offers insight into the preservation of local musical knowledge through lived community practice. The findings provide implications for integrating community-based pedagogy into traditional music education curricula in Indonesia